2012
DOI: 10.1007/978-3-642-30284-8_44
|View full text |Cite
|
Sign up to set email alerts
|

Generating Possible Interpretations for Statistics from Linked Open Data

Abstract: Abstract. Statistics are very present in our daily lives. Every day, new statistics are published, showing the perceived quality of living in different cities, the corruption index of different countries, and so on. Interpreting those statistics, on the other hand, is a difficult task. Often, statistics collect only very few attributes, and it is difficult to come up with hypotheses that explain, e.g., why the perceived quality of living in one city is higher than in another. In this paper, we introduce Explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 14 publications
0
34
0
1
Order By: Relevance
“…The interpretation turns out to be an intensive and time-consuming process, where part of knowledge can remain unrevealed or unexplained. Explain-a-LOD [106] is one of the first approaches in the literature for automatically generating hypothesis for explaining statistics by using LOD. The tool uses FeGeLOD (described in Section 7.1) for enhancing statistical datasets with background information from DBpedia, and uses correlation analysis and rule learning for producing hypothesis which are presented to the user.…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation turns out to be an intensive and time-consuming process, where part of knowledge can remain unrevealed or unexplained. Explain-a-LOD [106] is one of the first approaches in the literature for automatically generating hypothesis for explaining statistics by using LOD. The tool uses FeGeLOD (described in Section 7.1) for enhancing statistical datasets with background information from DBpedia, and uses correlation analysis and rule learning for producing hypothesis which are presented to the user.…”
Section: Discussionmentioning
confidence: 99%
“…publishing statistical data and interpretation of statistics [5], improving tourism experience [6], pharmaceutical R&D data sharing [7], crowdsourcing in emergency management [4], etc. A few years ago, our analysis of the adoption of Semantic Web technologies by enterprises [2] has shown that companies benefit from features that improve data sharing and re-use (57 %), improve searching (57 %), allow incremental modelling (26 %), explicit content relation (24 %), identifying new relationships (17 %), dynamic content generation (14 %), personalization (10 %), open modeling (12 %), rapid response to change (10 %), reducing time to market (5 %), and automation (5 %).…”
Section: Towards a Broader Adoptionmentioning
confidence: 99%
“…In addition, Paulheim [18] employed datasets that are published on the Linked Data Web in order to enrich statistical data with attributes e.g. from DBpedia.…”
Section: Related Workmentioning
confidence: 99%